Bisnis Alternatif Perempuan di Era Informasi - Tri Soesantari; Fahriza Isvandiari (Universitas Muhammadiyah Sidoarjo, 2017)
In order to support its roles in the domestic and public sectors, many women have the ability in using information communication technology. In the other hand, women are still exposed to gender imbalances. The position of women is not only different, but also lose or less unequal than men. This approach used descriptive qualitative to describe alternative business that gotten by women to get justice through online business. The development of information technology brings a new atmosphere, where previously the women work offline to online. Business is developed by women such as making cakes with known brands as Kampung Roti, clothing, marketing of Lapis Surabaya cake, and knitting. Starting an online business is not easier for women, struggling to master technology is not easily where women have to be familiar with software and hardware. They should also search the network to find customers and highlight their own business. Women should organize their online businesses with a technique, having the financial capital, searching the models, materials, mastering selling buying online systems, moreover also finding out what opportunities are available. Through information technology, women who work online can get equal position with men